Graffiti als Interaktionsform. Geritzte Inschriften in den Wohnhäusern Pompejis - Lohmann, Polly (2018)
The excavations at Pompeii have uncovered over 5600 graffiti carved into the walls of temples, shops, workshops, and homes. They range in type from literary verses, names, greetings, and messages to numbers and tally marks. For the first time, this book takes a comprehensive look at Pompeii’s never-before systematically researched graffiti to explore the nature of graffiti writing in ancient times.